(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Oi Kampasi Agrotourism Development Strategy In Sukadamai Village Manggelewa District Dompu Regency West Nusa Tenggara Province. Oi Kampasi Agrotourism is a natural open space agrotourism that combines nature tourism with agricultural tourism, providing an attraction in the form of fruit and vegetable picking tourism which is equipped with bathing tours. This agrotourism located in Sukadamai Village, Manggelewa District, Dompu Regency, West Nusa Tenggara Province. Oi Kampasi Agrotourism is classified as underdeveloped agrotourism. The purpose of this study was to identify internal and external factors that affect Oi Kampasi Agrotourism, and to design a strategy for developing Oi Kampasi Agrotourism. Collecting data in this study using Focus Group Discussion (FGD) and structured interviews. This study uses the SWOT analysis method. The results of this study indicate that the IE matrix analysis falls into cell V, where Oi Kampasi Agrotourism can apply a Growth Strategy with product development and market penetration. The alternative strategies resulting from the SWOT analysis are SO strategy (promoting, cooperating, and creating superior commodities), ST strategy (forming an agreement with wild buffalo owners and compiling regulations to be applied), WO strategy (diversifying plant species, seeking private investors for investment, and establishing cooperative relationships), and WT strategies (conducting agricultural extension, reforestation, and establishing security officers).